Toxoplasma gondii (Eucoccidia: Sarcoystidae) dissemination pattern in rats after oral infection with oocysts of an avirulent strain - Guerrero, Olga M (Universidad de Costa Rica, 1996)
Differences in Toxoplasma gondii dissemination in white rats (Sprague Dowley) and mice (Wistar) after oral oocyst inoculation are described. Groups of five anirnals (both hosts) were infected per os with oocysts of the TCR-2 avirulent strain and the dissemination pattero was compared in brain tissue or by serology. Early dissemination was similar in both species. One hr after infection the parasite was present in blood and peritoneal exudate as well as in heart, lupg, liver, spleen, lymph nodes and brain. However, after five days there were important differences between both hosts and after 30 days, the parasite was detected only in rat heart and brain, while in mice it persisted in fluids and all organs